Penerapan Program Linear Fuzzy dalam Optimalisasi Jumlah Produksi dan Keuntungan di K-Bakery - Sitanggang, Nelita Anggraini; Mustika, Mira (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
K-Bakery is a bakery located in Bandar Lampung City, Lampung. K-Bakery produces various types of bread, namely brown bread, nuts, greentea, mocha, and tiramisu bread which involve various raw material resources. Unstable market demand creates obstacles for K-Bakery in formulating the number of each type of bread to be produced so as to produce maximum profit. However, in determining the amount of production must pay attention to the limited supply of raw materials. In this case, there is a need for production planning so that all available resources can be used optimally and produce a combination of production that provides maximum profit. One way to solve this problem is to optimize production using a fuzzy linear program with a tolerance of 10% as the capability of K-Bakery. The use of the fuzzy linear program generates greater profits than the usual linear program, the profit obtained is Rp. 11.247.972,1708by producing 320 chocolate breads, 449,75 peanut breads, 365,667 greentea breads, 250 moka breads fruit, 449,925 srikaya bread, and 499,975 tiramisu breads. In addition, the value of l = 0,5 is obtained, or in other words, the maximum addition of each raw material is 50% of the available safety stock.